Prognostic Value of Epithelial Cell Adhesion Molecules in T1‐2N0M0 Glottic Cancer. (28th December 2020) - Murakami, Naoya; Mori, Taisuke; Machida, Ryunosuke; Kodaira, Takeshi; Ito, Yoshinori; Shikama, Naoto; Konishi, Koji; Matsumoto, Yasuo; Murakami, Yuji; Nakamura, Naoki; Yamashita, Hideomi; Yorozu, Atsunori; et al.
Abstract : Objective: This is an ancillary study of a multi‐institutional randomized non‐inferiority phase III trial of accelerated fractionation (AF) versus standard fractionation (SF) radiation therapy for T1‐2N0M0 glottic cancer (JCOG0701). Biopsy specimens of tumors from the patients enrolled in the JCOG0701 are collected and the association between clinical outcomes and histopathologic features such as expression of epithelial cell adhesion molecule (EpCAM), p53, and p16 were investigated. Methods: Five slices of undyed slides from biopsy specimens were sent to the National Cancer Center Hospital and all the specimens were assessed for the expression of EpCAM, p53, and p16. The primary objective was to investigate the association between 3‐year progression‐free survival (PFS) and expression of EpCAM, p53, and p16. Results: A total of 88 out of 370 patients were enrolled in this ancillary study. The 3‐year PFS for tumors with strong expression of EpCAM was 70.6% (95% CI 43.1%–86.6%), while that of tumors without strong expression of EpCAM was 77.5% (95% CI 65.9%–85.5%) with no remarkable difference between groups ( P = .67). Likewise, there was no significant difference in 3‐year PFS between tumors regardless of p53 or p16 status. However, in a subgroup analysis for 17 patients with a strong expression of EpCAM, AF showed better 3‐year PFS than SF (100% vs 54.5%, P = .07). Conclusions: From the current study, it could not be concluded that EpCAM, p16, and p53 were prognostic factors for early‐stage glottic cancer after primary radiation therapy. AF might be an appropriate fractionation for tumors with a strong expression of EpCAM. Level of Evidence: 3 Laryngoscope, 131:1522–1527, 2021